(3EQSGd GdMQGH dbJd GdZQGH (B((3ebGeI(B)s - (3YHO GdSdGe Hf eLGgO Hf TgGHs
(3ChdgG (B:s
(3hHYO CjgG GdTbjb GdefUa Efj CQKj dc GdReGf HdaX cGdLeGf, hef jbhd Ydqj eGf, aCUZ hYdjc GdCeGf, cGf ef bHd QMjH GdQMGH, fLjH GdUMGH s
(3BNQgG (B:s
(3HLGg CLd GdeQSdjf eMeO hCcQe gGO bGe Gddg OGYjG Ydjg UdGI Gddg Ke SdGeg hBd hCUMGH hef cGf JGdjG s
(3HgG BKGQ QWhHI WGZjI LYdJ GdJUhjQ eXdekG aj HYV GdUaMGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B20 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs